Հայաստանի համացանցային ԶԼՄ-ի կազմավորման և զարգացման շրջափուլերը - Ա. Ռ. Ավետիսյան (ՀՀ ԳԱԱ հրատ.)
История интернет-СМИ охватывает приблизительно 20-летний период, но за это короткое время пережила несколько важных этапов развития и подверглась реструктуризации. Данные процессы не обошли стороной и Армению. The history of the internet media covers approximately 20-year period, but in that short period has experienced several important stages of development and has undergone restructuring. These processes concern Armenia, too.
Keywords: Bibliography; Language and Literature; Information resources; Electronic information resources; PNJ Journalism; The periodical Press, etc